A century of ambivalence : the Jews of Russia and the Soviet Union, 1881 to the present - Gitelman, Zvi Y. 1940- (Schocken Books, 1988)
From the introduction: A hundred years ago, the Russian Empire contained the largest Jewish community in the world, numbering about five million people. Today, the Jewish population of the former Soviet Union has dwindled to half a million, but remains probably the world's third largest Jewish community. In the intervening century the Jews of that area have been at the center of some of the most dramatic events of modern history-two world wars, revolutions, pogroms, political liberation, repression, and the collapse of the USSR. They have gone through tumultuous upward and downward economic and social mobility and experienced great enthusiasms and profound disappointments. In startling photographs from the archives of the YIVO Institute for Jewish Research and with a lively and lucid narrative, A Century of Ambivalence traces the historical experience of Jews in Russia from a period of creativity and repression in the second half of the 19th century through the paradoxes posed by the post-Soviet era. This redesigned edition, which includes more than 200 photographs and two substantial new chapters on the fate of Jews and Judaism in the former Soviet Union, is ideal for general readers and classroom use. Zvi Gitelman is Professor of Political Science and Director of the Jean and Samuel Frankel Center for Judaic Studies at the University of Michigan. He is author of Jewish Nationality and Soviet Politics: The Jewish Sections of the CPSU, 1917-1930 and editor of Bitter Legacy: Confronting the Holocaust in the USSR (Indiana University Press). Published in association with YIVO Institute for Jewish Research Contents Introduction Creativity versus Repression: The Jews in Russia, 1881-1917 Revolution and the Ambiguities of Liberation Reaching for Utopia: Building Socialism and a New Jewish Culture The Holocaust The Black Years and the Gray, 1948-1967 Soviet Jews, 1967-1987: To Reform, Conform, or Leave? The "Other" Jews of the Former USSR: Georgian, Central Asian, and Mountain Jews The Post-Soviet Era: Winding Down or Starting Up Again? The Paradoxes of Post-Soviet Jewry